LITERATURE-BASED LEARNING TO BUILD STUDENTS’ VOCABULARY - Puspitasari, Evi (Journal of Foreign Language Teaching and Learning, 2016)
Literature-based Approach (LbA) is popularly used in reading. In implementing the approach, teachers use literary works to be read by students. The literary works that the students read to get the language input are commonly authentic which means that by reading the texts, students can identify a model of language and several aspects of language such as expression, vocabulary, grammar, and culture and how to use them in a real context. Realizing the importance of input, a teacher in a university in Indonesia implemented this approach in a reading class for freshmen. This research which belongs to descriptive qualitative research put attention on investigating what the students perceived toward the implementation of the LbA to assist them in vocabulary building. The data were collected by interviewing five students who were chosen because it was their first time reading an English language novel and they were the top six students in terms of vocabulary scores. To interview the participants who are presented using pseudonym, a semi guided interview guide- line was used as an instrument. The research results show that students were anxious joining this class at the beginning. However, after some meetings and reading several pages, they started to enjoy reading the novel because the novel was interesting and entertaining. In addition, the topic was closely related to their daily life. After getting new words, one of participants wrote them on paper and stuck it on her room wall. Four other students wrote the words on a notebook as a vocabulary journal. Besides by doing those things to help them recall the words, the students also used them in retelling quizzes for writing and in daily conversation with mates for speaking.